Fuzzy-PI Current Controlled D-STATCOM - Coteli, Resul; Dandil, Besir; Ata, Fikret (Gazi Univ, 2011)
Effort for improvement of power quality in distribution systems has been gradually increased. Traditionally, fixed, mechanical switched reactor/capacitor banks and Static Var Compensator have been used for improving the power quality issue in distribution systems. In recent years, applications of inverter based power quality conditioner have been growing for reactive power compensation in distribution systems, since their response is faster than that of the conventional compensators. Distribution STATCOM (D-STATCOM) is an inverter based power quality conditioner device used to improve the power quality issues in distribution systems. Control of D-STATCOM is generally realized by PI controllers with fixed parameter. However, desired control performance couldn't be obtained due to its nonlinear structure. In this paper, Fuzzy-PI controller which has a nonlinear and robust structure is proposed for control of D-STATCOM's d and q-axis currents. Simulation of Fuzzy-PI current controlled D-STATCOM is performed by MATLAB/Simulink software. In simulation study, the dynamic response of D-STATCOM is observed by changing the reference reactive current. Simulation results compared with conventional PI controller are given.
Keywords: Reactive power compensation; power quality conditioner; D-STATCOM; Fuzzy-PI